Efficacy of vitamin C supplementation as an adjunct in the non-surgical management of periodontitis: a systematic review - Hytham N. Fageeh; Hammam I. Fageeh; Ashwin Prabhu; Shilpa Bhandi; Shahrukh Khan; Shankargouda Patil (Systematic Reviews, 2021)
Abstract Background and objective The antioxidant potential of vitamin C is useful in reducing oxidative stress, free radicals, and reactive oxygen species, which may assist in the improved outcomes of periodontal therapy. This systematic review was aimed to evaluate the effectiveness of vitamin C supplementation as an adjunct to non-surgical periodontal therapy, in the management of periodontitis. Data sources PubMed, EMBASE, Cochrane Library, and Web of Science. Study eligibility criteria Randomized controlled trials published between January 1990 and March 2020. Participants People 18 years and older with periodontitis. Study appraisal and synthesis methods The Critical Appraisal Skills Programme (CASP) quality appraisal tool. Results The initial search yielded 441 articles out of which six studies fulfilled the inclusion criteria. Vitamin C supplementation helped improve bleeding indices in gingivitis but did not significantly lead to reduction of probing depths or clinical attachment gain for periodontitis. Conclusion Administration of vitamin C as an adjunct to non-surgical periodontal therapy did not result in clinically significant improvements in pocket probing depths at 3 months in periodontitis patients. With the limited evidence available, no recommendation can be made for supplementation of vitamin C in conjunction with initial periodontal therapy for subjects with periodontitis to improve primary treatment outcome measures.